2022
DOI: 10.1038/s41531-022-00404-w
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal clinical and biomarker characteristics of non-manifesting LRRK2 G2019S carriers in the PPMI cohort

Abstract: We examined 2-year longitudinal change in clinical features and biomarkers in LRRK2 non-manifesting carriers (NMCs) versus healthy controls (HCs) enrolled in the Parkinson’s Progression Markers Initiative (PPMI). We analyzed 2-year longitudinal data from 176 LRRK2 G2019S NMCs and 185 HCs. All participants were assessed annually with comprehensive motor and non-motor scales, dopamine transporter (DAT) imaging, and biofluid biomarkers. The latter included cerebrospinal fluid (CSF) Abeta, total tau and phospho-ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Other studies have also confirmed the longitudinal progression of both motor and non-motor symptoms, including autonomic dysfunction, EDS, and cognitive impairment (Amara et al, 2017;Simuni et al, 2018;Stanković et al, 2019;Myers et al, 2022). It should be noted that a subset of symptoms have shown stability, relief, and improvement in longitudinal studies (Cilia et al, 2020;Simuni et al, 2022). However, despite these inconsistencies, most studies have reported an overall deterioration of motor and non-motor symptoms, consistent with our data.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have also confirmed the longitudinal progression of both motor and non-motor symptoms, including autonomic dysfunction, EDS, and cognitive impairment (Amara et al, 2017;Simuni et al, 2018;Stanković et al, 2019;Myers et al, 2022). It should be noted that a subset of symptoms have shown stability, relief, and improvement in longitudinal studies (Cilia et al, 2020;Simuni et al, 2022). However, despite these inconsistencies, most studies have reported an overall deterioration of motor and non-motor symptoms, consistent with our data.…”
Section: Discussionsupporting
confidence: 89%
“…Second, mutations in LRRK2 are the most common cause of a monogenic form of clinically typical PD although the proportion of asymptomatic carriers developing symptoms may be lower than initially predicted. 93 Yet, strikingly, LBs are not detectable in a substantial fraction of patients with LRRK2 mutations analyzed postmortem, and this pattern has been confirmed in patients with several disease-causing mutations in this gene (Table 1). 15,94 In some of these LRRK2 patients, tau-positive pathology is found.…”
Section: Mendelian Forms Of Pdmentioning
confidence: 89%
“…This mutation might increase the susceptibility of DA neurons to degeneration. Interestingly, in a recent longitudinal clinical study with carriers of the G2019S mutation, which do not manifest symptoms, 13% of the patients had a significant reduction in the dopamine transporter (DAT) in the caudate putamen [8], which indicates neurochemical alterations before the disease develops. In order to investigate the roles of LRRK2, and mutated LRRK2, in the development of Parkinsonism, several rodent models bearing the G2019S mutation have been generated using, for example, bacterial artificial chromosome (BAC) and knock-in (KI) to express human or murine LRRK2 or LRRK2-G2019S [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%